Non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2023502214
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2022-01-28
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2042-01-28
Smart Images

Figure 0007634075000005 
Figure 0007634075000006 
Figure 0007634075000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrolyte secondary battery. This application claims priority based on Patent Application No. 2021-030396, filed in Japan on February 26, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] A nonaqueous electrolyte secondary battery is provided in a sealed container with a pair of polarizable electrodes consisting of a positive electrode and a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte solution impregnated in the positive electrode, the negative electrode, and the separator and containing a supporting salt and a nonaqueous solvent such as an organic solvent. Such nonaqueous electrolyte secondary batteries have a high energy density and are lightweight, and are therefore used in the power source units of electronic devices, power storage units that absorb fluctuations in the amount of power generated by power generation devices, and the like.
[0003] In addition, silicon oxide (SiO x Since non-aqueous electrolyte secondary batteries containing ) can obtain a high discharge capacity, they are used particularly as small non-aqueous electrolyte secondary batteries such as coin type (button type). Such coin type non-aqueous electrolyte secondary batteries are known to have excellent charge / discharge characteristics with high voltage and high energy density, as well as a long cycle life and high reliability. For this reason, non-aqueous electrolyte batteries have conventionally been used as backup power sources for semiconductor memories and clock functions in various small electronic devices such as mobile phones, PDAs, portable game consoles, and digital cameras (see, for example, Patent Document 1).
[0004] In addition, in non-aqueous electrolyte secondary batteries, for example, an organic electrolyte solution using a cyclic carbonate ester, a chain carbonate ester, or a mixture thereof as a solvent is used as the electrolyte solution. Patent Document 1 discloses the use of an electrolyte solution containing cyclic carbonate solvents ethylene carbonate (hereinafter sometimes referred to as EC) and propylene carbonate (hereinafter sometimes referred to as PC), and a chain ether solvent dimethoxyethane (hereinafter sometimes referred to as DME) in a predetermined ratio, and further containing 0.6 to 1.4 mol / L of an imide salt (LiFSI or LiTFSI) as a supporting salt, for the purpose of enabling operation over a wide temperature range.
[0005] The nonaqueous electrolyte secondary battery described in Patent Document 1 is a coin-type nonaqueous electrolyte secondary battery with a discharge current of about 5 to 25 μA, used for backing up the memory of mounted devices, and has sufficient discharge capacity over a wide temperature range, including low temperature environments. More specifically, Patent Document 1 uses EC and PC as organic solvents to maintain discharge capacity in high temperature environments, and further uses DME as an organic solvent to improve low temperature characteristics. Furthermore, since it is usually difficult to obtain a sufficient discharge capacity if the concentration of the supporting electrolyte is too high, Patent Document 1 specifies the concentration of the supporting electrolyte to be 0.6 to 1.4 mol / L. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2016 / 143543 Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, with the miniaturization of various electronic devices, small-sized coin-type nonaqueous electrolyte secondary batteries are sometimes required to be used as main power sources, not just as memory backups. In such applications, nonaqueous electrolyte secondary batteries are required to be small and have high capacity, as well as high output characteristics that allow them to supply large currents. However, in the case of small-sized coin-type nonaqueous electrolyte secondary batteries, there is a problem that it is difficult to obtain high output characteristics with the composition of the electrolyte solution provided in conventional nonaqueous electrolyte secondary batteries, as disclosed in Patent Document 1.
[0008] The present invention has been made in view of the above problems, and has an object to provide a nonaqueous electrolyte secondary battery that can supply a large current over a wide temperature range, can maintain a sufficient discharge capacity even when discharging at the mA level, and can obtain high output and high capacity despite its small size. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to solve the above problems, and have repeatedly conducted experiments to supply a large current over a wide temperature range and maintain a sufficient discharge capacity in a small non-aqueous electrolyte secondary battery such as a coin type. As a result, the composition of the organic solvent and supporting salt used in the electrolyte was adjusted, Manufacturing By optimizing the overall battery structure as well as the individual components, it has been discovered that even a small non-aqueous electrolyte secondary battery can achieve both high output and high capacity.
[0010] That is, the inventors first used a mixed solvent of a cyclic carbonate solvent having a structure represented by the following (chemical formula 1) and a chain ether solvent having a structure represented by the following (chemical formula 2) as an organic solvent contained in the electrolyte, and adjusted the mixing ratio of each solvent. Manufacturing By doing so, they found that it is possible to improve low-temperature characteristics without compromising capacity characteristics at room temperature or capacity retention rate at high temperatures.
[0011] [ka]
[0012] In the above (Chemical Formula 1), R1, R2, R3, and R4 each represent any one of hydrogen, fluorine, chlorine, an alkyl group having 1 to 3 carbon atoms, and a fluorinated alkyl group. In addition, R1, R2, R3, and R4 in the above (Chemical Formula 1) may be the same or different.
[0013] [ka]
[0014] In the above (chemical formula 2), R 5 , R 6 represents any one of hydrogen, fluorine, chlorine, an alkyl group having 1 to 3 carbon atoms, and a fluorinated alkyl group. 5 , R 6 may be the same or different.
[0015] Furthermore, the present inventors have further repeatedly carried out experiments and investigations on the cyclic carbonate solvent (chemical formula 1) and the chain ether solvent (chemical formula 2) that constitute the above mixed solvent. As a result, it was first found that by using ethylene carbonate (EC) and propylene carbonate (PC) as the cyclic carbonate solvent represented by (chemical formula 1), the capacity retention rate can be favorably maintained, particularly at high temperatures. In addition, it was found that by using dimethoxyethane (DME) as the chain ether solvent represented by (chemical formula 2), it is possible to improve low-temperature characteristics in particular while maintaining the capacity at room temperature. In addition, the mixing ratio of the above EC, PC and DME was adjusted. Manufacturing It has been found that by doing so, the effect of maintaining the discharge capacity can be significantly obtained, particularly in a low temperature environment.
[0016] The present inventors then determined that the solvent used in the electrolyte solution had the above composition, and adjusted the composition and content of the supporting salt. ManufacturingBy optimizing the battery, the researchers found that even small non-aqueous electrolyte secondary batteries such as coin-type batteries can supply large currents over a wide temperature range, including low-temperature environments, and achieve high output characteristics.
[0017] Furthermore, the inventors discovered that by combining a configuration in which the composition of the above-mentioned electrolyte is optimized with a configuration in which the arrangement of each battery element inside the storage container is optimized, the above-mentioned high output characteristics and high capacity characteristics can be obtained more significantly, and thus completed the present invention.
[0018] That is, the nonaqueous electrolyte secondary battery of the present invention includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator disposed between the positive electrode and the negative electrode, an electrolytic solution including an organic solvent and a supporting salt, and a storage container in which the positive electrode, the negative electrode, the separator, and the electrolytic solution are disposed in an internal storage space, and at least one of the positive electrode and the negative electrode is in the form of a pellet including an active material, a conductive assistant, and a binder, the separator is made of a nonwoven fabric of glass fiber, the electrolytic solution includes a mixed solution of propylene carbonate (PC), ethylene carbonate (EC), and dimethoxyethane (DME) as the organic solvent in a volume ratio range of {PC:EC:DME}={0.5-1.5:0.5-1.5:1-3}, and includes lithium bis(fluorosulfonyl)imide (LiFSI) at 2-7 (mol / L) as the supporting salt.
[0019] According to the present invention, first, by using an organic solvent for the electrolyte solution having the above composition, an increase in the viscosity of the electrolyte solution in a low-temperature environment of room temperature to -30 to -40°C can be prevented, and the impediment of charge transfer can be suppressed. As a result, discharge characteristics in a low-temperature environment are improved, and sufficient discharge capacity can be maintained over a wide temperature range. Specifically, first, by using PC and EC as the cyclic carbonate solvent, which have a high dielectric constant and a high solubility of the supporting salt, it becomes possible to obtain a large discharge capacity. In addition, since PC and EC have a high boiling point, the electrolyte is difficult to volatilize even if it is used or stored in a high temperature environment. In addition, by mixing EC with PC, which has a lower melting point than EC, as a cyclic carbonate solvent, it is possible to improve low-temperature properties. In addition, the use of DME, which has a low melting point, as a chain ether solvent improves low-temperature characteristics. In addition, DME has low viscosity, which improves the electrical conductivity of the electrolyte. Furthermore, DME solvates with Li ions, which increases the discharge capacity of non-aqueous electrolyte secondary batteries. Furthermore, by using an electrolyte containing LiFSI, which has excellent electrical conductivity, in the molar ratio within the above range as a supporting electrolyte, a large current can be obtained even in a small nonaqueous electrolyte secondary battery. Also, by containing LiFSI in the above molar ratio in the electrolyte, the voltage drop at the beginning of discharge can be suppressed to a certain range, so that a sufficient discharge capacity can be maintained.
[0020] Moreover, in the nonaqueous electrolyte secondary battery of the present invention having the above configuration, the electrolyte solution contains the supporting salt lithium bis(fluorosulfonyl)imide (LiFSI) at 4 to 7 (mol / L).
[0021] According to the present invention, by using a supporting salt containing LiFSI having excellent electrical conductivity in the above-mentioned molar ratio range as the electrolyte, the electrical characteristics, more specifically the overdischarge characteristics, of the nonaqueous electrolyte secondary battery after storage under high temperature, high humidity and overdischarge conditions are further improved. This makes it possible to more effectively prevent the deterioration of the nonaqueous electrolyte secondary battery even if overdischarge occurs. In addition, by using an electrolyte containing LiFSI in the above-mentioned range, the internal resistance of the nonaqueous electrolyte secondary battery can be effectively reduced.
[0022] Furthermore, the nonaqueous electrolyte secondary battery of the present invention has the above-mentioned configuration, and is characterized in that the storage container is a coin-shaped container including a cylindrical positive electrode can with a bottom, and a negative electrode can that is fixed to an opening of the positive electrode can with a gasket interposed therebetween and forms a storage space between the positive electrode can and the negative electrode can, and the storage space is sealed by crimping the opening of the positive electrode can against the negative electrode can.
[0023] According to the present invention, the battery elements are arranged in the storage space of a storage container in which the positive electrode can and the negative electrode can are sealed in an optimal structure, resulting in a structure with excellent electrical insulation and sealing properties, which can prevent the volatilization of the electrolyte and the intrusion of moisture in the air into the battery. As a result, even a small coin-type nonaqueous electrolyte secondary battery can remarkably obtain the above-mentioned high output characteristics and high capacity characteristics.
[0024] In addition, the nonaqueous electrolyte secondary battery of the present invention has the above-mentioned configuration, and is characterized in that the storage container has a structure in which the gasket is interposed between the inner bottom and inside of the positive electrode can and the negative electrode can, thereby providing an insulating and sealed structure.
[0025] According to the present invention, an insulating and sealing structure is adopted in which a gasket is interposed in an optimal position between the positive electrode can and the negative electrode can, thereby further improving electrical insulation and sealing properties. As a result, as described above, even in a small coin-type nonaqueous electrolyte secondary battery, outstanding high output characteristics and high capacity characteristics can be obtained.
[0026] Furthermore, the nonaqueous electrolyte secondary battery of the present invention is characterized in that in the above-mentioned configuration, i.e., a configuration employing an insulating and sealing structure in which a gasket is interposed between the inner bottom and inside of the positive electrode can and the negative electrode can, the electrolyte contains 3 to 4 (mol / L) of lithium bis(fluorosulfonyl)imide (LiFSI) as the supporting salt.
[0027] According to the present invention, in a non-aqueous electrolyte secondary battery employing an insulating and sealing structure in which a gasket is interposed between the inner bottom and inner side of the positive electrode can and the negative electrode can, a supporting salt containing LiFSI having excellent electrical conductivity in the above-mentioned range is used for the electrolyte, thereby making it possible to obtain a large current and maintain a sufficient discharge capacity. As a result, even in a small coin-type non-aqueous electrolyte secondary battery, similar to the above, excellent high-output characteristics and high-capacity characteristics can be more remarkably obtained.
[0028] Moreover, in the nonaqueous electrolyte secondary battery of the present invention, in the above configuration, the storage container is structured such that the positive electrode is disposed so as to cover the entire surface of an inner bottom part of the positive electrode can, and the gasket is interposed between the inner side of the positive electrode can and between the positive electrode and the negative electrode can, thereby providing an insulating and sealing structure.
[0029] According to the present invention, the positive electrode is disposed so as to cover the entire inner bottom of the positive electrode can, and a gasket is interposed between the inner side of the positive electrode can and between the positive electrode and the negative electrode can, thereby improving electrical insulation and sealing properties as described above. As a result, even in a small coin-type nonaqueous electrolyte secondary battery, excellent high output characteristics and high capacity characteristics can be remarkably obtained.
[0030] Moreover, in the nonaqueous electrolyte secondary battery of the present invention having the above configuration, the electrolyte solution contains the supporting salt lithium bis(fluorosulfonyl)imide (LiFSI) at 2 to 3 (mol / L).
[0031] According to the present invention, in a non-aqueous electrolyte secondary battery having an insulating and sealed structure in which a positive electrode is disposed so as to cover the entire inner bottom of a positive electrode can and a gasket is interposed between the inside of the positive electrode can and between the positive electrode and the negative electrode can, a large current can be obtained and a sufficient discharge capacity can be maintained by using a supporting salt for the electrolyte containing LiFSI having excellent electrical conductivity in a molar ratio within the above range. As a result, even in a small coin-type non-aqueous electrolyte secondary battery, similar to the above, excellent high output characteristics and high capacity characteristics can be more remarkably obtained.
[0032] Further, in the non-aqueous electrolyte secondary battery of the present invention, in the above configuration, the positive electrode contains, as the positive electrode active material, at least Li 1+x Co y Mn 2-x-y a lithium manganese oxide represented by O4 (0 ≦ x ≦ 0.33, 0 < y ≦ 0.2).
[0033] According to the present invention, since the positive electrode contains the compound having the above composition as the lithium manganese oxide used for the positive electrode active material, the effects of stabilizing the high output characteristics and the high capacity characteristics are obtained.
[0034] Further, in the non-aqueous electrolyte secondary battery of the present invention, in the above configuration, the negative electrode contains, as the negative electrode active material, SiO having at least a part of its surface coated with carbon X (0 < X < 2).
[0035] According to the present invention, by using SiO having its surface coated with carbon X (0 < X < 2) as the negative electrode active material in the negative electrode, the conductivity of the negative electrode is improved, the increase in the internal resistance in a low temperature environment is suppressed, so that the voltage drop at the initial stage of discharge is suppressed, the high capacity characteristics are more stabilized, and a large current can be stably supplied, and the high output characteristics are also more stabilized.
Advantages of the Invention
[0036] According to the non-aqueous electrolyte secondary battery of the present invention, first, by using PC and EC in an optimal ratio as the organic solvent for the electrolytic solution, operation in a wide temperature range becomes possible, and by using DME in an optimal ratio, the low temperature characteristics are improved, so that the electric conductivity of the electrolytic solution is improved. In addition, since the electrolytic solution contains LiFSI as the supporting salt within an optimal range, both high output characteristics and high capacity characteristics can be obtained. Furthermore, by combining the electrolytic solution with an optimized composition and the configuration in which the arrangement structure of each battery element inside is optimized, it is possible to provide a non-aqueous electrolyte secondary battery that is small in size, excellent in high output characteristics, and also excellent in high capacity characteristics. [Brief description of the drawings]
[0037] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic diagram of a coin-type nonaqueous electrolyte secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic diagram of a coin-type nonaqueous electrolyte secondary battery according to another embodiment of the present invention. [Figure 3A] FIG. 3A is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the capacity characteristics of a nonaqueous electrolyte secondary battery, and is a graph showing the change in capacity when discharging is performed with the molar concentration of a supporting salt contained in the electrolyte being changed, the end-of-discharge voltage being set to 1.0 V, and the discharge current being set to 1 mA. [Figure 3B] FIG. 3B is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the capacity characteristics of a nonaqueous electrolyte secondary battery, and is a graph showing the change in capacity when discharging is performed with the molar concentration of a supporting salt contained in the electrolyte changed, the discharge cut-off voltage set to 1.0 V, and the discharge current set to 7 mA. [Figure 4] FIG. 4 is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the power characteristics and capacity characteristics of the nonaqueous electrolyte secondary battery, and is a graph showing the relationship between the discharge current and the capacity when the molar concentrations of the supporting salts contained in the electrolyte are set to 1 to 7 mol / L, the discharge current is set to 1 to 8 mA, and the end-of-discharge voltage is set to 1.0 V. [Figure 5A] FIG. 5A is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the effect of increasing the discharge capacity of a nonaqueous electrolyte secondary battery, and is a graph showing the relationship between the discharge current and the relative value when the discharge capacity at a supporting salt concentration of 1 M is taken as 1, when the molar concentrations of the supporting salts contained in the electrolyte are set to 1 to 7 mol / L and the battery is discharged at an end-of-discharge voltage of 2.0 V. [Figure 5B]FIG. 5B is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the effect of increasing the discharge capacity of a nonaqueous electrolyte secondary battery, and is a graph showing the relationship between the discharge current and the relative value when the discharge capacity at a supporting salt concentration of 1 M is taken as 1, when the molar concentrations of the supporting salts contained in the electrolyte are set to 1 to 7 mol / L and the battery is discharged at an end-of-discharge voltage of 1.0 V. [Figure 6A] FIG. 6A is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the capacity characteristics of a nonaqueous electrolyte secondary battery, and is a graph showing the change in capacity when the molar concentration of a supporting salt contained in the electrolyte is changed, the end-of-discharge voltage is set to 1.0 V, and the battery is discharged at 1 mA. [Figure 6B] FIG. 6B is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the capacity characteristics of a nonaqueous electrolyte secondary battery, and is a graph showing the change in capacity when the molar concentration of a supporting salt contained in the electrolyte is changed, the end-of-discharge voltage is set to 1.0 V, and the battery is discharged at 7 mA. [Figure 7A] FIG. 7A is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the effect of increasing the discharge capacity of a nonaqueous electrolyte secondary battery, and is a graph showing the relationship between the discharge current and the relative value when the discharge capacity at a supporting salt concentration of 1 M is taken as 1, in the case where the molar concentrations of the supporting salts contained in the electrolyte are 1 to 7 mol / L and the discharge end voltage is 1.0 V. [Figure 7B] FIG. 7B is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the effect of increasing the discharge capacity of a nonaqueous electrolyte secondary battery, and is a graph showing the relationship between the discharge current and the relative value when the discharge capacity at a supporting salt concentration of 1 M is taken as 1, in the case where the molar concentrations of the supporting salts contained in the electrolyte are 1 to 7 mol / L and the discharge end voltage is 2.0 V. [Figure 8A] FIG. 8A is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the capacity characteristics of a nonaqueous electrolyte secondary battery, and is a graph showing the change in capacity when the molar concentration of a supporting salt contained in the electrolyte is changed, the end-of-discharge voltage is set to 1.0 V, and the battery is discharged at 1 mA. [Figure 8B] FIG. 8B is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the capacity characteristics of a nonaqueous electrolyte secondary battery, and is a graph showing the change in capacity when the molar concentration of a supporting salt contained in the electrolyte is changed, the end-of-discharge voltage is set to 1.0 V, and the battery is discharged at 7 mA. [Figure 9A] FIG. 9A is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the effect of increasing the discharge capacity of a nonaqueous electrolyte secondary battery, and is a graph showing the relationship between the discharge current and the relative value when the discharge capacity at a supporting salt concentration of 1 M is taken as 1, in the case where the molar concentrations of the supporting salts contained in the electrolyte are 1 to 7 mol / L and the discharge end voltage is 1.0 V. [Figure 9B] FIG. 9B is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the effect of increasing the discharge capacity of a nonaqueous electrolyte secondary battery, and is a graph showing the relationship between the discharge current and the relative value when the discharge capacity at a supporting salt concentration of 1 M is taken as 1, in the case where the molar concentrations of the supporting salts contained in the electrolyte are 1 to 7 mol / L and the discharge end voltage is 2.0 V. [Figure 10A] FIG. 10A is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the transition of the internal resistance of a nonaqueous electrolyte secondary battery in a high-temperature, high-humidity storage test, and is a graph showing the relationship between the number of days stored in a high-temperature, high-humidity environment and the transition of the internal resistance when the molar concentrations of the supporting salts contained in the electrolyte are set to 1 to 7 mol / L, respectively. [Figure 10B] FIG. 10B is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the rate of increase in internal resistance of a nonaqueous electrolyte secondary battery after a high-temperature, high-humidity storage test, and is a graph showing the relationship between the number of moles of the supporting salt and the rate of increase in internal resistance after storage for each number of days when the molar concentration of the supporting salt contained in the electrolyte is 1 to 7 mol / L and the number of days of storage in a high-temperature, high-humidity environment is 7 to 40 days. [Figure 11A]FIG. 11A is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the transition of the capacity of a nonaqueous electrolyte secondary battery that has been overdischarged after a high-temperature, high-humidity storage test, and is a graph showing the relationship between the number of moles of the supporting salt and the discharge capacity and the capacity retention rate when the molar concentrations of the supporting salts contained in the electrolyte are set to 1 to 7 mol / L and the storage period is set to 28 days. [Figure 11B] FIG. 11B is a diagram for explaining an example of a nonaqueous electrolyte secondary battery according to the present invention, and is a diagram for explaining the transition of the capacity of a nonaqueous electrolyte secondary battery that has been overdischarged after a high-temperature, high-humidity storage test, and is a graph showing the relationship between the number of moles of the supporting salt and the discharge capacity and the capacity retention rate when the molar concentrations of the supporting salts contained in the electrolyte are set to 1 to 7 mol / L and the storage period is set to 40 days. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] Hereinafter, embodiments of the nonaqueous electrolyte secondary battery of the present invention will be described in detail with reference to the drawings. The nonaqueous electrolyte secondary battery described in the present invention specifically comprises an active material used as a positive electrode or a negative electrode and an electrolyte solution housed in a container, but the configuration according to the present invention can also be applied to electrochemical cells such as lithium ion capacitors.
[0039] <First embodiment> A nonaqueous electrolyte secondary battery 1 according to a first embodiment of the present invention will now be described with reference to FIG.
[0040] [Configuration of non-aqueous electrolyte secondary battery] 1 is a so-called coin (button) type battery. The nonaqueous electrolyte secondary battery 1 is generally configured to include, in a storage container 2, a positive electrode 10 containing a positive electrode active material and capable of absorbing and releasing lithium ions, a negative electrode 20 containing a negative electrode active material and capable of absorbing and releasing lithium ions, a separator 30 disposed between the positive electrode 10 and the negative electrode 20, a gasket 40 for sealing the storage space of the storage container 2, and an electrolyte solution 50 containing at least a supporting salt and an organic solvent.
[0041] The nonaqueous electrolyte secondary battery 1 of this embodiment is provided with a storage container 2 that has a cylindrical positive electrode can 12 with a bottom, and a cylindrical (hat-shaped) negative electrode can 22 with a lid that is fixed to an opening 12a of the positive electrode can 12 with a gasket 40 interposed therebetween and forms a storage space between the positive electrode can 12 and the negative electrode can 22, and that seals the storage space by crimping the peripheral edge of the opening 12a of the positive electrode can 12 inward, i.e., toward the negative electrode can 22.
[0042] In the storage space sealed by the storage container 2, a positive electrode 10 provided on the positive electrode can 12 side and a negative electrode 20 provided on the negative electrode can 22 side are disposed opposite each other with a separator 30 interposed therebetween, and further, the storage space is filled with an electrolyte 50. In the example shown in FIG. 1, a lithium foil 60 is interposed between the negative electrode 20 and the separator 30. As shown in FIG. 1, gasket 40 is inserted along the inner circumferential surface of positive electrode can 12 and is connected to the outer periphery of separator 30 to hold separator 30 in place. The positive electrode 10, the negative electrode 20 and the separator 30 are impregnated with an electrolyte solution 50 filled in the storage container 2.
[0043] In the nonaqueous electrolyte secondary battery 1 of the example shown in Fig. 1, the positive electrode 10 is electrically connected to the inner surface of the positive electrode can 12 via the positive electrode current collector 14, and the negative electrode 20 is electrically connected to the inner surface of the negative electrode can 22 via the negative electrode current collector 24. Note that in this embodiment, the nonaqueous electrolyte secondary battery 1 including the positive electrode current collector 14 and the negative electrode current collector 24 as illustrated in Fig. 1 is described as an example, but the present invention is not limited thereto, and for example, a configuration in which the positive electrode can 12 also serves as the positive electrode current collector and the negative electrode can 22 also serves as the negative electrode current collector may be used.
[0044] The nonaqueous electrolyte secondary battery 1 of the present embodiment is configured as described above, and is capable of storing (charging) and releasing (discharging) electric charge by the movement of lithium ions from one of the positive electrode 10 and the negative electrode 20 to the other.
[0045] In the nonaqueous electrolyte secondary battery 1 of this embodiment, at least one of the positive electrode 10 and the negative electrode 20 is in the form of a pellet containing an active material, a conductive additive, and a binder, and the separator 30 is made of a nonwoven fabric of glass fibers. The nonaqueous electrolyte secondary battery 1 includes an electrolyte solution 50 containing a mixed solution of propylene carbonate (PC), ethylene carbonate (EC), and dimethoxyethane (DME) as an organic solvent in a volume ratio range of {PC:EC:DME}={0.5-1.5:0.5-1.5:1-3}, and containing lithium bis(fluorosulfonyl)imide (LiFSI) at 2-7 (mol / L) as a supporting salt.
[0046] (Positive and negative electrode cans) 1, the storage container 2 used in the nonaqueous electrolyte secondary battery 1 of this embodiment includes a cylindrical positive electrode can 12 with a bottom, and a negative electrode can 22 that is fixed to an opening 12a of the positive electrode can 12 via a gasket 40, which will be described in detail later, and forms a storage space between the positive electrode can 12 and the negative electrode can 22. The storage container 2 is a roughly coin-shaped (button-shaped) container in which the storage space is sealed by crimping the opening 12a of the positive electrode can 12 to the negative electrode can 22. For this reason, the maximum inner diameter of the positive electrode can 12 is larger than the maximum outer diameter of the negative electrode can 22.
[0047] As described above, the positive electrode can 12 constituting the storage container 2 is configured in a bottomed cylindrical shape and has a circular opening 12a in a plan view. The material of such a positive electrode can 12 can be any conventionally known material without any restrictions, and examples of the material include stainless steels such as SUS316L and SUS329J4. Other conventionally known stainless steels may also be used. Furthermore, metal materials other than stainless steels may also be used for the positive electrode can 12.
[0048] As described above, the negative electrode can 22 is configured in a covered cylindrical shape (hat shape) and its tip 22a is configured to enter the positive electrode can 12 from the opening 12a. The material for such a negative electrode can 22 may be a conventionally known stainless steel, similar to the material for the positive electrode can 12. For example, SUS316L, SUS329J4L, etc., may be used, similar to the material for the positive electrode can 12. Furthermore, other conventionally known stainless steels, such as SUS304-BA, may also be used. Furthermore, a metal material other than stainless steel may be used for the negative electrode can 22. 22 The negative electrode can 22 may be made of a clad material made of, for example, stainless steel pressure-welded with copper or nickel.
[0049] The thickness of the metal plate material used for positive electrode can 12 and negative electrode can 22 is generally about 0.1 to 0.3 mm, and for example, positive electrode can 12 and negative electrode can 22 can be configured to have an average thickness of about 0.20 mm over the entirety.
[0050] 1, the tip portion 22a of the negative electrode can 22 is folded back along the outer side surface of the negative electrode can 22, but this is not limited thereto. For example, the present invention can be applied to the case where a negative electrode can 22 that does not have the above-mentioned folded back shape is used, in which the tip portion 22a is an end face of a metal plate.
[0051] In addition, examples of nonaqueous electrolyte secondary batteries to which the configuration described in detail in this embodiment can be applied include batteries of various sizes in addition to the 920 size (outer diameter φ9.5 mm × height 2.0 mm), which is a common size for coin-type nonaqueous electrolyte secondary batteries.
[0052] According to the nonaqueous electrolyte secondary battery 1 of this embodiment, each battery element is disposed in the storage space of the storage container 2 in which the positive electrode can 12 and the negative electrode can 22 are sealed in an optimal structure, resulting in a structure with excellent sealing properties, which can effectively prevent the volatilization of the electrolyte solution 50 and the intrusion of moisture contained in the air into the battery. Therefore, even in a small coin-type nonaqueous electrolyte secondary battery, high output characteristics and high capacity characteristics can be obtained by combining the electrolyte solution 50 having an optimized composition of the organic solvent and supporting salt with a battery structure, as will be described in detail later.
[0053] 1 has a structure in which the storage container 2 is insulated and sealed by interposing a gasket 40, which will be described later, between the inner bottom 12b and inner part 12c of the positive electrode can 12 and the negative electrode can 22. In this embodiment, the electrical insulation and sealing properties are further improved by adopting an insulating and sealing structure in which the gasket 40 is optimally disposed between the positive electrode can 12 and the negative electrode can 22. When such a structure is combined with the composition of the electrolyte 50, which will be described later in detail, both excellent high output characteristics and high capacity characteristics can be more significantly obtained even in a small coin-type nonaqueous electrolyte secondary battery 1 as in the illustrated example.
[0054] (gasket) As shown in FIG. 1, gasket 40 is formed in an annular shape along the inner circumferential surface of positive electrode can 12, and tip portion 22a of negative electrode can 22 is disposed inside annular groove 41 thereof.
[0055] Examples of materials for such gasket 40 include plastic resins such as polypropylene resin (PP), polyphenyl sulfide (PPS), polyethylene terephthalate (PET), polyamide, liquid crystal polymer (LCP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resin (PFA), polyether ether ketone resin (PEEK), polyether nitrile resin (PEN), polyether ketone resin (PEK), polyarylate resin, polybutylene terephthalate resin (PBT), polycyclohexane dimethylene terephthalate resin, polyether sulfone resin (PES), polyamino bismaleimide resin, polyether imide resin, and fluororesin. Among these, using polypropylene resin for gasket 40 is preferable from the viewpoint of preventing the gasket from being significantly deformed during use or storage in a high-temperature environment and further improving the sealing property of the nonaqueous electrolyte secondary battery.
[0056] Furthermore, the above-mentioned materials to which glass fiber, mica whiskers, ceramic powder, etc. are added in an amount of 30 mass% or less can also be suitably used for the gasket 40. By using such materials, it is possible to suppress the gasket from being significantly deformed by high temperatures and prevent the electrolyte 50 from leaking.
[0057] A sealant may be applied to the inner surface of the annular groove of the gasket 40. As such a sealant, asphalt, epoxy resin, polyamide resin, butyl rubber adhesive, etc. may be used. After the sealant is applied to the inside of the annular groove 41, it is dried before use.
[0058] Gasket 40 is sandwiched between positive electrode can 12 and negative electrode can 22 and is at least partially compressed; however, the compression ratio at this time is not particularly limited and may be within a range that can reliably seal the inside of nonaqueous electrolyte secondary battery 1 and that does not cause breakage of gasket 40.
[0059] (electrolyte) As described above, the electrolyte solution 50 used in the nonaqueous electrolyte secondary battery 1 of this embodiment contains, as an organic solvent, a mixed solution of propylene carbonate (PC), ethylene carbonate (EC), and dimethoxyethane (DME) in a volume ratio range of {PC:EC:DME}={0.5-1.5:0.5-1.5:1-3}, and contains, as a supporting salt, lithium bis(fluorosulfonyl)imide (LiFSI) at 2-7 (mol / L). Such electrolyte solution 50 is usually made by dissolving a supporting salt in a non-aqueous solvent such as an organic solvent, and its properties are determined taking into consideration the heat resistance, viscosity, and other properties required of electrolyte solution 50.
[0060] In general, when an electrolytic solution containing an organic solvent is used in a non-aqueous electrolyte secondary battery, the poor solubility of lithium salts results in a large temperature dependency of electrical conductivity, and the characteristics at low temperatures are significantly reduced compared to those at room temperature. On the other hand, when, for example, an asymmetric structure ethyl methyl carbonate or acetate esters, which are chain carbonate esters, are used as the organic solvent of the electrolytic solution in order to improve low-temperature characteristics, the opposite is true: the characteristics of the non-aqueous electrolyte secondary battery at high temperatures are reduced. Even when an organic solvent such as ethyl methyl carbonate is used in the electrolytic solution, the solubility of lithium salts is still poor, and there is a limit to improving low-temperature characteristics.
[0061] In addition, in order to obtain high output characteristics capable of supplying a large current in a small coin-type non-aqueous electrolyte secondary battery, it is necessary to adjust the type and content of the supporting salt within the optimum range in addition to the composition of the organic solvent in the electrolyte. Manufacturing It was necessary to do so.
[0062] For this reason, in this embodiment, first, a mixed solvent containing cyclic carbonate solvents PC and EC and a chain ether solvent DME in an appropriate mixing ratio is used as the organic solvent for the electrolytic solution 50. This makes it possible to obtain a nonaqueous electrolyte secondary battery 1 that can maintain a sufficient discharge capacity over a wide temperature range, including low temperature environments.
[0063] Specifically, by using PC and EC, which have a high dielectric constant and a high solubility of the supporting salt, as the cyclic carbonate solvent, the discharge capacity of the nonaqueous electrolyte secondary battery 1 is increased. In addition, since PC and EC have high boiling points, the electrolyte is unlikely to volatilize even if the battery is used or stored in a high-temperature environment. In addition, by mixing EC with PC, which has a lower melting point than EC, as a cyclic carbonate solvent, it is possible to improve low-temperature properties. In addition, the use of DME, which has a low melting point, as a chain ether solvent improves low-temperature characteristics. In addition, DME has low viscosity, which improves the electrical conductivity of the electrolyte. Furthermore, DME solvates with Li ions, which increases the discharge capacity of non-aqueous electrolyte secondary batteries.
[0064] The cyclic carbonate solvent has a structure represented by the following (chemical formula 1), and examples thereof include propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC), trifluoroethylene carbonate (TFPC), chloroethylene carbonate (ClEC), trifluoroethylene carbonate (TFEC), difluoroethylene carbonate (DFEC), vinylene carbonate (VEC), etc. In the nonaqueous electrolyte secondary battery 1 according to the present invention, in particular, from the viewpoints of ease of forming a film on the electrode on the negative electrode 20 and improving low-temperature characteristics, and further improving the capacity retention rate at high temperatures, two types of cyclic carbonate solvents, PC and EC, are used as the cyclic carbonate solvent having the structure represented by the following (chemical formula 1).
[0065] [ka]
[0066] In the above (Chemical Formula 1), R1, R2, R3, and R4 each represent any one of hydrogen, fluorine, chlorine, an alkyl group having 1 to 3 carbon atoms, and a fluorinated alkyl group. In addition, R1, R2, R3, and R4 in the above (Chemical Formula 1) may be the same or different.
[0067] In this embodiment, as described above, by using PC and EC, which have a high dielectric constant and a high solubility of the supporting salt, as the cyclic carbonate solvent, it is possible to obtain a large discharge capacity. In addition, since PC and EC have high boiling points, the electrolyte is unlikely to volatilize even when used or stored in a high-temperature environment. Furthermore, by using PC, which has a lower melting point than EC, as the cyclic carbonate solvent in combination with EC, excellent low-temperature characteristics are obtained.
[0068] The chain ether solvent has a structure represented by the following (chemical formula 2), and examples thereof include 1,2-dimethoxyethane (DME) and 1,2-diethoxyethane (DEE). In this embodiment, in particular, from the viewpoint of improving the electrical conductivity and further improving the low-temperature characteristics while maintaining the capacity at room temperature, DME, which is easily solvated with lithium ions, is used as a chain ether solvent having a structure represented by the following (chemical formula 2).
[0069] [ka]
[0070] In the above (Chemical Formula 2), R5 and R6 each represent any one of hydrogen, fluorine, chlorine, an alkyl group having 1 to 3 carbon atoms, and a fluorinated alkyl group. R5 and R6 may be the same or different.
[0071] In this embodiment, as described above, the low-temperature characteristics are improved by using DME, which has a low melting point, as the chain ether solvent. In addition, since DME has a low viscosity, the electrical conductivity of the electrolyte is improved. Furthermore, since DME solvates with Li ions, a large discharge capacity can be obtained as a nonaqueous electrolyte secondary battery.
[0072] In this embodiment, the blending ratio of each organic solvent in the solvent of the electrolytic solution 50 is set in the range of {PC:EC:DME}=0.5-1.5:0.5-1.5:1-3 by volume. The blending ratio in the solvent is more preferably in the range of 0.8-1.2:0.8-1.2:1.5-2.5 by volume, and most preferably about {PC:EC:DME}={1:1:2}. When the blending ratio of the organic solvent is in the above range, the effect of improving low-temperature characteristics without impairing the capacity retention rate at high temperature or room temperature as described above can be more significantly obtained.
[0073] More specifically, when the blending ratio of propylene carbonate (PC), which is a cyclic carbonate solvent, is equal to or higher than the lower limit of the above range, the effect of improving low-temperature properties can be significantly obtained by mixing PC, which has a lower melting point than EC, with EC. On the other hand, since PC has a lower dielectric constant than EC, the concentration of the supporting electrolyte cannot be increased, and therefore if the content is too high, it may be difficult to obtain a large discharge capacity. Therefore, it is preferable to limit the blending ratio to the upper limit of the above range.
[0074] Furthermore, if the blending ratio of ethylene carbonate (EC), which is a cyclic carbonate solvent, in the organic solvent is equal to or higher than the lower limit of the above range, the dielectric constant of the electrolyte 50 and the solubility of the supporting salt are increased, and the discharge capacity of the nonaqueous electrolyte secondary battery is increased. On the other hand, EC has poor electrical conductivity due to its high viscosity, and also has a high melting point, so if the EC content is too high, there is a possibility that the low-temperature properties will deteriorate. Therefore, it is preferable to limit the blending ratio to the upper limit of the above range. Furthermore, by setting the blending ratio of EC in the organic solvent within the above range, it is possible to suppress an increase in internal resistance in a low-temperature environment.
[0075] In addition, if the blending ratio of dimethoxyethane (DME), a chain ether solvent, in the organic solvent is set to the lower limit of the above range or higher, the low-temperature characteristics can be significantly improved by the inclusion of a certain amount of DME, which has a low melting point, in the organic solvent. In addition, since DME has low viscosity, it improves electrical conductivity and can obtain a large discharge capacity by solvating with Li ions. On the other hand, since DME has a low dielectric constant, the concentration of the supporting electrolyte cannot be increased, and therefore if the content is too high, it may be difficult to obtain a large discharge capacity. Therefore, it is preferable to limit the blending ratio to the upper limit of the above range. Furthermore, by setting the blending ratio of DME in the organic solvent within the above range, it becomes possible to suppress the voltage drop during initial discharge.
[0076] In the nonaqueous electrolyte secondary battery 1 of this embodiment, lithium bis(fluorosulfonyl)imide (LiFSI) is used as a supporting salt in the electrolytic solution 50, and its content in the electrolytic solution 50 is set to a range of 2 to 7 mol / L. The content of the supporting salt (LiFSI) in the electrolytic solution 50 can be determined within the above range, taking into consideration the type of the positive electrode active material described below.
[0077] By containing LiFSI, which has excellent electrical conductivity, as a supporting salt in the molar ratio range above in addition to the organic solvent contained in the electrolytic solution 50 having the above composition, a large current can be obtained even in a small nonaqueous electrolyte secondary battery such as a coin type. In addition, by containing LiFSI in the molar ratio range above in the electrolytic solution 50, the voltage drop at the beginning of discharge can be suppressed to a certain range, so that a sufficient discharge capacity can be maintained even in mA-level discharge.
[0078] Furthermore, although the detailed mechanism is not clear, by including the supporting salt made of the lithium compound in the electrolyte 50 at an optimal molar concentration, a necessary and sufficient amount of lithium can be secured even if the electrolyte deteriorates. This provides the effect of suppressing the decrease in discharge capacity even during long-term storage or use.
[0079] If the supporting salt concentration in the electrolyte 50 exceeds the upper limit of the above range, the effect of maintaining the discharge capacity and the effect of increasing the discharge current will plateau, and if it falls below the lower limit, although a certain effect in improving the low-temperature characteristics can be seen, it becomes difficult to obtain the effect of maintaining the discharge capacity and the effect of increasing the discharge current. Therefore, since a supporting salt concentration that is too high or too low in the electrolyte 50 may adversely affect the battery characteristics, it is preferable to set it within the above range.
[0080] In this embodiment, it is more preferable that the supporting salt concentration in the electrolytic solution 50, that is, the concentration of LiFSI, is 4 to 7 (mol / L). By setting the concentration of LiFSI having excellent conductivity in the electrolyte 50 within the above range, although the detailed mechanism is not clear, the electrical characteristics, specifically the overdischarge characteristics, of the nonaqueous electrolyte secondary battery after storage under high temperature, high humidity and overdischarge conditions are improved. This provides an effect of preventing deterioration of the nonaqueous electrolyte secondary battery even when overdischarge occurs. Similarly, by setting the concentration of LiFSI in the electrolyte 50 within the above range, the internal resistance of the nonaqueous electrolyte secondary battery can be effectively reduced, although the detailed mechanism is not clear.
[0081] In addition, when the storage container 2 has a structure in which the storage container 2 is insulated and sealed by interposing a gasket 40 described later between the inner bottom 12b and the inner part 12c of the positive electrode can 12 and the negative electrode can 22, it is preferable that the electrolyte 50 contains 3 to 4 (mol / L) of LiFSI as a supporting salt. In the coin-type nonaqueous electrolyte secondary battery 1 having an insulating and sealed structure as shown in FIG. 1, by limiting the content of LiFSI contained in the electrolyte 50 to the above range, a larger current can be generated and a sufficient discharge capacity can be maintained. As a result, the small-sized coin-type nonaqueous electrolyte secondary battery 1 can obtain better high-output characteristics and high-capacity characteristics.
[0082] In this embodiment, as described above, first, by setting the organic solvent used in the electrolytic solution 50 to the above composition, it is possible to prevent the viscosity of the electrolytic solution from increasing particularly in a low-temperature environment of normal temperature to -30 to -40°C, and suppress the hindrance of charge movement. As a result, the discharge characteristics in a low-temperature environment are improved, and it becomes possible to maintain a sufficient discharge capacity in a wide temperature range.
[0083] (Positive electrode) The positive electrode 10 is not particularly limited as long as it contains a positive electrode active material composed of lithium manganese oxide, and those conventionally known in this field can be used. Further, as the positive electrode 10, in addition to the above positive electrode active material, polyacrylic acid as a binder and graphite or the like as a conductive auxiliary agent can be mixed and formed into, for example, a pellet shape for use.
[0084] Examples of the positive electrode active material contained in the positive electrode 10 include lithium manganese oxides such as LiMn2O4 having a spinel crystal structure and Li4Mn5O 12 and the like. Among such lithium manganese oxides, in particular, those in which a part of Mn is substituted with Co, such as Li 1+x Co y Mn 2-x-y O4 (0 ≦ x ≦ 0.33, 0 < y ≦ 0.2), are preferable. Thus, by using a positive electrode active material in which a transition metal element such as Co or Ni is added to lithium manganese oxide and a part of it is substituted with the transition metal element, the discharge characteristics are further improved, and the effects of more stable high output characteristics and capacity characteristics can be obtained.
[0085] In this embodiment, by using a positive electrode active material composed of lithium manganese oxide having the above composition for the positive electrode 10, even in the small button-type non-aqueous electrolyte secondary battery 1 as described above, operation in a wide temperature range becomes possible, and excellent high output characteristics and high capacity characteristics can be obtained more remarkably. Further, in this embodiment, the positive electrode active material may contain not only one kind but also a plurality of the above lithium manganese oxides.
[0086] When a granular positive electrode active material made of the above materials is used, the particle size (D50) is not particularly limited and is, for example, preferably 0.1 to 100 μm, more preferably 10 to 50 μm, and even more preferably 20 to 40 μm. If the particle size (D50) of the positive electrode active material is less than the lower limit of the above-mentioned preferred range, the nonaqueous electrolyte secondary battery becomes difficult to handle due to increased reactivity when exposed to high temperatures, and if it exceeds the upper limit, the discharge rate may decrease. In the present invention, the "particle size (D50) of the positive electrode active material" refers to the median size of the particle measured by a conventionally known laser diffraction method.
[0087] The content of the positive electrode active material in the positive electrode 10 is determined taking into consideration the discharge current, discharge capacity, and the like required for the nonaqueous electrolyte secondary battery 1, and is preferably, for example, 50 to 95 mass %. When the content of the positive electrode active material is equal to or more than the lower limit of the above preferred range, sufficient discharge current and discharge capacity are easily obtained, and when it is equal to or less than the preferred upper limit, the effect of making it easier to form the positive electrode 10 is obtained.
[0088] The positive electrode 10 may contain a conductive assistant (hereinafter, the conductive assistant used in the positive electrode 10 may be referred to as a "positive electrode conductive assistant"). Examples of the positive electrode conductive assistant include carbonaceous materials such as furnace black, ketjen black, acetylene black, and graphite. The positive electrode conductive assistant may be used alone or in combination of two or more of the above. The content of the positive electrode conductive assistant in the positive electrode 10 is preferably 1 to 25 mass %, more preferably 2 to 15 mass %. When the content of the positive electrode conductive assistant is equal to or greater than the lower limit of the above-mentioned preferred range, sufficient conductivity is easily obtained. Furthermore, when the electrode is molded into a pellet, it is easy to mold it. On the other hand, when the content of the positive electrode conductive assistant in the positive electrode 10 is equal to or less than the upper limit of the above-mentioned preferred range, sufficient discharge capacity is easily obtained by the positive electrode 10.
[0089] The positive electrode 10 may contain a binder (hereinafter, the binder used in the positive electrode 10 may be referred to as a "positive electrode binder"). As the positive electrode binder, a conventionally known substance can be used, and examples thereof include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), polyacrylic acid (PA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and the like. Among these, polyacrylic acid is preferable, and cross-linked polyacrylic acid is more preferable. The positive electrode binder may be one of the above-mentioned materials, or a combination of two or more of them. When polyacrylic acid is used as the positive electrode binder, the polyacrylic acid is adjusted to a pH of 3 to 10 in advance. Manufacturing In this case, the pH adjustment Manufacturing For example, an alkali metal hydroxide such as lithium hydroxide or an alkaline earth metal hydroxide such as magnesium hydroxide can be used. The content of the positive electrode binder in the positive electrode 10 can be, for example, 1 to 20 mass %.
[0090] The size of the positive electrode 10 is determined according to the size of the nonaqueous electrolyte secondary battery 1 . In addition, the thickness of the positive electrode 10 when housed inside the positive electrode can 12 is also determined according to the size of the nonaqueous electrolyte secondary battery 1, and is set to about 300 to 1000 μm when the nonaqueous electrolyte secondary battery 1 is, for example, a coin-type battery for use as a backup battery for various electronic devices.
[0091] The positive electrode 10 can be produced by a conventionally known production method. For example, a method for manufacturing the positive electrode 10 includes mixing a positive electrode active material and, if necessary, at least one of a positive electrode conductive assistant and a positive electrode binder to form a positive electrode mixture, and then pressure-molding the positive electrode mixture into a pellet shape such as a disk shape. The pressure to be applied when forming the positive electrode 10 by the above-mentioned pressure molding is determined taking into consideration the type of the positive electrode conductive assistant, and is, for example, 0.2 to 5 ton / cm.2 can be set as
[0092] As the positive electrode current collector 14, a conventionally known one can be used. For example, it may be made of a conductive resin adhesive using carbon as a conductive filler.
[0093] Here, as described above, in the non-aqueous electrolyte secondary battery 1 of the present embodiment, at least one of the positive electrode 10 and the negative electrode 20 is configured in a pellet shape. In the present embodiment, when the positive electrode 10 is configured in a pellet shape, the pellet-shaped positive electrode 10 is disposed in a through-hole portion of a gasket 40 configured in a ring shape in a plan view, which will be described in detail later, at the inner bottom portion 12b of the positive electrode can 12. In such a configuration, a conventionally known conductive adhesive is disposed between the inner bottom portion 12b of the positive electrode can 12 and the positive electrode 10, that is, between the positive electrode current collector 14 disposed on the inner bottom portion 12b of the positive electrode can 12 shown in FIG. 1 and the positive electrode 10, so that the positive electrode 10 and the inner bottom portion 12b are adhered via the positive electrode current collector 14.
[0094] (Negative electrode) The negative electrode 20 used in the present embodiment includes, as a negative electrode active material, SiO X (0 < X < 2). As the negative electrode 20, in addition to the above negative electrode active material, a mixture of a suitable binder, polyacrylic acid as a binder, and graphite or the like as a conductive assistant can be used, for example, in a pellet shape.
[0095] As the negative electrode active material used for the negative electrode 20, first, SiO or SiO2, that is, the above SiO x (0 < X < 2) represented by silicon oxide. By using silicon oxide having the above composition as the negative electrode active material, it becomes possible to use the non-aqueous electrolyte secondary battery 1 at a high voltage and the cycle characteristics are improved. Further, the negative electrode 20 may contain, as a negative electrode active material, at least any one of Li-Al alloy, Si, WO2, and WO3, which are alloy-based negative electrodes other than carbon, in addition to the above SiO x (0 < X < 2). By using the above material as the negative electrode active material in the negative electrode 20, the reaction between the electrolyte 50 and the negative electrode 20 in the charge-discharge cycle can be suppressed, the decrease in capacity can be prevented, and the effect of improving the cycle characteristics can be obtained.
[0096] Furthermore, at least a part of the surface of the negative electrode 20 is covered with carbon (C), and the negative electrode 20 contains a negative electrode active material composed of SiO x (0 < X < 2). By doing so, the conductivity of the negative electrode 20 is improved, and in particular, the increase in internal resistance in a low-temperature environment is suppressed. As a result, the voltage drop at the initial stage of discharge is suppressed, the high-capacity characteristics including the initial capacity are more stabilized, a large current can be stably supplied, and the effect of more stabilizing the high-output characteristics can be obtained. In addition, when using the above SiO x (0 < X < 2) as the negative electrode active material, it is sufficient that at least a part of the surface of the particles composed of SiO x (0 < X < 2) is covered with carbon, but it is preferable that the entire surface is covered from the viewpoint that the above effects become more prominent.
[0097] In addition, the method for covering the particle surface of SiO x (0 < X < 2) with carbon is not particularly limited, and examples thereof include physical vapor deposition (PVD) using a gas containing an organic substance such as methane or acetylene, and chemical vapor deposition (CVD).
[0098] As the negative electrode active material, SiO with at least a part of its surface covered with carbon xWhen (0 < X < 2) is used, the particle diameter (D50) is not particularly limited, but for example, 0.1 to 30 μm is preferable, and 1 to 10 μm is more preferable. If the particle diameter (D50) of the negative electrode active material is within the above range, when the non-aqueous electrolyte secondary battery is charged and discharged, even when expansion or contraction of the negative electrode occurs, the conductivity is maintained, so that a decrease in charge and discharge characteristics such as cycle characteristics is suppressed. If the particle diameter (D50) of the negative electrode active material is less than the lower limit value of the above preferable range, for example, when the non-aqueous electrolyte secondary battery is exposed to a high temperature, the reactivity increases and it becomes difficult to handle. On the other hand, if it exceeds the upper limit value, the discharge rate may decrease. Note that the particle diameter (D50) of the negative electrode active material (SiO x (0 < X < 2)) described in this specification is the particle diameter in a state where at least a part of the surface of SiO x (0 < X < 2) is coated with carbon.
[0099] Furthermore, in the present embodiment, the negative electrode active material in the negative electrode 20 contains both lithium (Li) and SiO X (0 < X < 2), and it is more preferable that the molar ratio (Li / SiO X ) thereof is in the range of 3.7 to 4.9. Thus, by including both lithium (Li) and SiO X in the negative electrode active material and setting the molar ratio thereof within the above range, an effect of preventing charging abnormalities and the like can be obtained.
[0100] If the above molar ratio (Li / SiO X ) is less than 3.7, since there is too little Li, for example, when used, stored, or preserved for a long time in a high-temperature environment, Li deficiency occurs and the discharge capacity decreases. On the other hand, if the above molar ratio (Li / SiO X ) exceeds 4.9, since there is too much Li, there is a possibility of charging abnormalities occurring. In addition, since metallic Li remains without being incorporated into SiO X , the internal resistance may increase and the discharge capacity may decrease.
[0101] Furthermore, in the present embodiment, the molar ratio (Li / SiO XIt is more preferable to select and set the above molar ratio (Li / SiO ) in the negative electrode active material in a more appropriate range depending on the type of the positive electrode active material contained in the positive electrode 10. For example, when lithium titanate is used as the positive electrode active material, the above molar ratio (Li / SiO ) in the negative electrode active material is set in a more appropriate range depending on the type of the positive electrode active material contained in the positive electrode 10. X It is more preferable that the molar ratio (Li / SiO ) is in the range of 4.0 to 4.7. When a lithium manganese oxide is used as the positive electrode active material, the above molar ratio (Li / SiO ) in the negative electrode active material is more preferable. X It is more preferable that the molar ratio (Li / SiO X ) within a range according to the type of positive electrode active material, the above-mentioned effect of suppressing an increase in initial resistance and preventing charging abnormalities and the like, and the effect of obtaining sufficient discharge capacity even when, for example, the battery is stored or used for a long period of time in a high-temperature environment, become more pronounced.
[0102] The content of the negative electrode active material in the negative electrode 20 is determined taking into consideration the discharge capacity required for the nonaqueous electrolyte secondary battery 1 and the like, and is, for example, preferably 50 mass % or more, more preferably 60 to 80 mass %. In the negative electrode 20, if the content of the negative electrode active material made of the above material is equal to or more than the lower limit of the above preferred range, a sufficient discharge capacity is easily obtained, and if it is equal to or less than the upper limit, the negative electrode 20 is easily formed.
[0103] The negative electrode 20 may contain a conductive assistant (hereinafter, the conductive assistant used in the negative electrode 20 may be referred to as a "negative electrode conductive assistant"). The negative electrode conductive assistant is similar to the positive electrode conductive assistant. The negative electrode 20 may contain a binder (hereinafter, the binder used in the negative electrode 20 may be referred to as the "negative electrode binder"). Examples of the negative electrode binder include polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), polyacrylic acid (PA), carboxymethyl cellulose (CMC), polyimide (PI), polyimide amide (PAI), and the like. Among these, polyacrylic acid is preferable, and cross-linked polyacrylic acid is more preferable. The negative electrode binder may be one of the above, or a combination of two or more of them. When polyacrylic acid is used as the negative electrode binder, the polyacrylic acid is adjusted to a pH of 3 to 10 in advance. Manufacturing In this case, the pH adjustment Manufacturing This can be achieved, for example, by adding an alkali metal hydroxide such as lithium hydroxide or an alkaline earth metal hydroxide such as magnesium hydroxide. The content of the negative electrode binder in the negative electrode 20 is, for example, 1 to 20 mass %.
[0104] The shape (for example, pellet-like), size, and thickness of the negative electrode 20 are similar to those of the positive electrode 10. In the nonaqueous electrolyte secondary battery 1 shown in FIG. 1, a lithium foil 60 is provided on the surface of the negative electrode 20, that is, between the negative electrode 20 and a separator 30 which will be described later.
[0105] As a method for manufacturing the negative electrode 20, for example, the above-mentioned material is used as the negative electrode active material, and if necessary, a negative electrode conductive assistant such as graphite and / or a negative electrode binder is mixed to prepare a negative electrode mixture, and the negative electrode mixture is pressure-molded into a pellet shape such as a disk shape. The pressure when the negative electrode 20 is pressure-molded is determined taking into consideration the type of the negative electrode conductive assistant, and is, for example, 0.2 to 5 ton / cm. 2 It can be said that:
[0106] The negative electrode current collector 24 may be made of the same material as the positive electrode current collector 14 .
[0107] As described above, in this embodiment, at least one of the positive electrode 10 and the negative electrode 20 is formed in a pellet shape. For example, when the negative electrode 20 is formed in a pellet shape, the pellet-shaped negative electrode 20 is disposed in the through-hole of the gasket 40 formed in a ring shape in a plan view inside the negative electrode can 22, as in the case of the positive electrode 10. In this configuration, a conventionally known conductive adhesive is disposed between the inner top 22b of the negative electrode can 22 and the negative electrode 20, that is, between the negative electrode current collector 24 disposed in the inner top 22b of the negative electrode can 22 in the example shown in FIG. 1 and the pellet-shaped negative electrode 20, so that the negative electrode 20 and the inner top 22b are bonded via the negative electrode current collector 24.
[0108] Also, lithium foil 60 is placed on the surface of negative electrode 20 after negative electrode 20 is placed inside negative electrode can 22 .
[0109] (Separator) The separator 30 is interposed between the positive electrode 10 and the negative electrode 20, and is made of an insulating film having high ion permeability, excellent heat resistance, and a predetermined mechanical strength. In this embodiment, a nonwoven fabric of glass fibers is used as the separator 30. Since glass fibers have excellent mechanical strength and high ion permeability, by using the nonwoven fabric of glass fibers for the separator 30, it is possible to reduce the internal resistance and improve the discharge capacity. The thickness of the separator 30 is determined taking into consideration the size of the nonaqueous electrolyte secondary battery 1, the material of the separator 30, and the like, and can be, for example, about 5 to 300 μm.
[0110] According to the nonaqueous electrolyte secondary battery 1 of the present embodiment, by combining a configuration in which the composition of the electrolytic solution 50 is optimized with a configuration in which the arrangement of each battery element inside the storage container 2 is optimized, it is possible to realize a nonaqueous electrolyte secondary battery 1 that is small in size yet has excellent high output characteristics and high capacity characteristics.
[0111] <Second embodiment> A nonaqueous electrolyte secondary battery according to a second embodiment of the present invention will be described below with reference to FIG. In the nonaqueous electrolyte secondary battery 100 according to the second embodiment described below, configurations similar to those of the nonaqueous electrolyte secondary battery 1 according to the first embodiment shown in FIG. 1 may be denoted by the same reference numerals and detailed descriptions thereof may be omitted.
[0112] As shown in FIG. 2, the nonaqueous electrolyte secondary battery 100 of the present embodiment is configured as a coin (button) type battery, similar to the nonaqueous electrolyte secondary battery 1 of the first embodiment shown in FIG. 1, and includes, in a storage container 102, a positive electrode 110 containing a positive electrode active material and capable of absorbing and releasing lithium ions, a negative electrode 120 containing a negative electrode active material and capable of absorbing and releasing lithium ions, a separator 130 disposed between the positive electrode 110 and the negative electrode 120, a gasket 140 for sealing the storage space of the storage container 102, and an electrolyte solution 50 containing at least a supporting salt and an organic solvent.
[0113] The nonaqueous electrolyte secondary battery 100 of this embodiment differs from the nonaqueous electrolyte secondary battery 1 of the first embodiment in that the storage container 102 has a structure in which the positive electrode 110 is disposed so as to cover the entire surface of the inner bottom 112b of the positive electrode can 112, and a gasket 140 is interposed between the inner part 112c of the positive electrode can 112 and between the positive electrode 110 and the negative electrode can 122 to provide an insulating and sealed structure.
[0114] According to the nonaqueous electrolyte secondary battery 100 of this embodiment, the above-mentioned insulating and sealing structure is adopted, thereby improving electrical insulation and sealing properties. Furthermore, as will be described in detail in the examples below, even a small coin-type nonaqueous electrolyte secondary battery can achieve even more excellent high-output characteristics and high-capacity characteristics.
[0115] In the nonaqueous electrolyte secondary battery 100 of this embodiment, the electrolyte 50 may have the same composition as that of the nonaqueous electrolyte secondary battery 1 of the above-described first embodiment. Meanwhile, in the present embodiment, the composition of the electrolytic solution 50 is the same as that of the nonaqueous electrolyte secondary battery 1 of the first embodiment in terms of the composition ratio of the organic solvent, while the content of the supporting salt LiFSI is more preferably in the range of 2 to 3 (mol / L).
[0116] By adopting the battery structure shown in FIG. 2 and setting the content of LiFSI in the electrolyte 50 to 2 to 3 (mol / L), which is lower than that in the first embodiment, both excellent high output characteristics and high capacity characteristics can be more significantly obtained. In the nonaqueous electrolyte secondary battery 100 of this embodiment, the detailed mechanism by which the above-mentioned effect is obtained by combining the above-mentioned battery structure with the composition of the electrolyte solution 50 is unclear. Outside diameter The present embodiment employs a structure in which the battery has a large positive electrode 110, and the positive electrode 110 is disposed so as to cover the entire surface of the inner bottom 112b of the positive electrode can 112. As a result, the distance between the negative electrode 120 and the positive electrode 110 is large due to the internal structure of the battery, and therefore, for example, the distance between the vicinity of the peripheral portion of the negative electrode 120 disposed inside the negative electrode can 122, which is smaller than the positive electrode can 112, and the vicinity of the peripheral portion of the positive electrode 110 is large. In this embodiment, it is believed that the above-mentioned effect is easily exhibited when an electrolyte solution having a lower concentration and a lower viscosity than that of the first embodiment is used by employing the above-mentioned structure.
[0117] According to the nonaqueous electrolyte secondary battery 100 of the present embodiment, similarly to the nonaqueous electrolyte secondary battery 1 of the first embodiment, by combining a configuration in which the composition of the electrolytic solution 50 is optimized with a configuration in which the arrangement of each battery element inside the storage container 102 is optimized, the battery is small in size, yet has excellent high output characteristics and high capacity characteristics.
[0118] <Other forms of non-aqueous electrolyte secondary batteries> In this embodiment, a coin-shaped nonaqueous electrolyte secondary battery including a container formed by crimping a stainless steel positive electrode can and a negative electrode can has been described as an embodiment of the nonaqueous electrolyte secondary battery, but the present invention is not limited thereto. For example, the present invention can be applied to a nonaqueous electrolyte secondary battery having a structure in which the opening of a ceramic container body is sealed with a ceramic lid by heat treatment such as seam welding using a metal sealing member.
[0119] Furthermore, the configuration according to the present invention can also be applied to electrochemical cells such as lithium ion capacitors.
[0120] <Applications of non-aqueous electrolyte secondary batteries> As described above, the nonaqueous electrolyte secondary battery 1 of the present embodiment can supply a large current over a wide temperature range, can maintain a sufficient discharge capacity even when discharging at the mA level, and can obtain high output characteristics and high capacity characteristics despite its small size. Therefore, for example, it can be suitably used as a main power source requiring a high current, in addition to a backup power source in various electronic devices.
[0121] <Action and effect> As described above, according to the nonaqueous electrolyte secondary battery 1,100 of the embodiment of the present invention, firstly, the use of PC and EC in an optimal ratio in the organic solvent as the electrolyte 50 enables operation over a wide temperature range, and the use of DME in an optimal ratio improves low-temperature characteristics, thereby improving the electrical conductivity of the electrolyte 50. In addition, the electrolyte 50 contains LiFSI in an optimal range as a supporting salt, thereby achieving both high output characteristics and high capacity characteristics. Furthermore, by combining the electrolyte solution 50 with an optimized composition with a configuration in which the arrangement structure of each battery element inside the storage container 2 is optimized, it is possible to provide a nonaqueous electrolyte secondary battery 1,100 that is a small coin-type battery but has excellent high-output characteristics and high-capacity characteristics. EXAMPLES
[0122] Next, the present invention will be described in more detail with reference to examples and comparative examples. Note that the scope of the present invention is not limited by these examples, and the nonaqueous electrolyte secondary battery according to the present invention can be modified appropriately without departing from the gist of the present invention.
[0123] <Preparation and Evaluation of Non-Aqueous Electrolyte Secondary Batteries> [Experimental Examples 1-7] In Experimental Examples 1 to 7, coin-type nonaqueous electrolyte secondary batteries were fabricated, in which the storage container 2 had a structure as shown in Fig. 1 in which a gasket 40 was interposed between the inner bottom 12b and inside part 12c of the positive electrode can 12 and the negative electrode can 22 to insulate and seal the storage container 2. In Experimental Examples 1 to 7, an electrolyte solution was prepared with the composition shown below to fabricate the nonaqueous electrolyte secondary batteries. In this experimental example, in the cross-sectional view shown in FIG. Outside diameter A coin-type (920 type) nonaqueous electrolyte secondary battery (lithium secondary battery) with a diameter of 9.5 mm and a thickness of 2.0 mm was fabricated.
[0124] (Preparation of electrolyte Manufacturing ) Prepare the organic solvent in the ratio (volume %) described below. Manufacturing A supporting salt was dissolved in the organic solvent to prepare an electrolyte solution. First, a mixed solvent was prepared by mixing propylene carbonate (PC), ethylene carbonate (EC), and dimethoxyethane (DME) in a volume ratio of {PC:EC:DME}={1:1:2} as an organic solvent. Manufacturing did. Next, lithium bis(fluorosulfonyl)imide (LiFSI) was dissolved as a supporting salt in the mixed solvent obtained, changing the concentration in 1M steps in the range of 1 to 7M (1 to 7mol / L), to prepare seven types of electrolyte solutions (Experimental Examples 1 to 7) with different concentrations of supporting salt. Manufacturing did.
[0125] (Battery Construction) As the positive electrode 10, first, commercially available lithium manganese oxide (Li 1.14 Co0.06 Mn 1.80 O4) was mixed with graphite as a conductive additive and polyacrylic acid as a binder in a ratio of lithium manganese oxide:graphite:polyacrylic acid=95:4:1 (mass ratio) to prepare a positive electrode mixture. Next, 56 mg of the obtained positive electrode mixture was 2 The mixture was pressed at a pressure of 1000 MPa and molded into a disk-shaped pellet having a diameter (φ) of 5.8 mm and a thickness (t) of 0.8 mm.
[0126] Next, the obtained pellet (positive electrode 10) was attached to the inner surface of a stainless steel (SUS329J4L: t = 0.2 mm) positive electrode can 12 using a carbon-containing conductive resin adhesive, and these were integrated to obtain a positive electrode unit. Thereafter, this positive electrode unit was dried by heating under reduced pressure at 120 °C for 11 hours in the atmosphere. Then, a sealant was applied to the inside surface of the opening 12a of the positive electrode can 12 in the positive electrode unit.
[0127] Next, SiO powder whose entire surface was covered with carbon (C) was prepared as the negative electrode active material for the negative electrode 20. Then, graphite as a conductive agent and polyacrylic acid as a binder were mixed with this negative electrode active material in a ratio of 75:20:5 (mass ratio) to prepare a negative electrode mixture. Next, 11.5 mg of the obtained negative electrode mixture was applied to 2 The mixture was pressed into a disk-shaped pellet having a diameter (φ) of 6.3 mm and a thickness (t) of 0.2 mm.
[0128] Next, the obtained pellet (negative electrode 20) was attached to the inner top 22b of a stainless steel (Cu-SUS304-Ni clad can: t=0.2 mm) negative electrode can 22 using a conductive resin adhesive containing carbon as a conductive filler, and these were integrated to obtain a negative electrode unit. Thereafter, this negative electrode unit was dried under reduced pressure and heating at 160°C for 11 hours in a vacuum. A lithium foil 60 punched into a disk shape having a diameter (φ) of 5.8 mm and a thickness (t) of 0.42 mm was then pressed onto the pellet-shaped negative electrode 20 to form a lithium-negative electrode laminate.
[0129] As described above, in this experimental example, the positive electrode current collector 14 and the negative electrode current collector 24 shown in FIG. 1 were not provided, and the positive electrode can 12 was given the function of the positive electrode current collector, and the negative electrode can 22 was given the function of the negative electrode current collector, to fabricate a nonaqueous electrolyte secondary battery.
[0130] Next, the nonwoven fabric made of glass fibers was dried and then punched into a disk shape with a diameter (φ) of 7.4 mm to form the separator 30. Then, this separator 30 was placed on the lithium foil 60 that had been pressure-bonded onto the negative electrode 20, and a polypropylene gasket 40 was placed on the opening of the negative electrode can 22.
[0131] Next, the positive electrode can 12 and the negative electrode can 22 are charged with the above-mentioned procedure. Manufacturing Each battery was filled with 30 μL of the electrolyte solution in total. For each of the seven types of electrolyte solutions (Experimental Examples 1 to 7) prepared by changing the concentration of the supporting salt, the above-mentioned components constituting the nonaqueous electrolyte secondary battery were prepared, and the electrolyte solution was filled into the positive electrode can 12 and the negative electrode can 22, respectively.
[0132] Next, the negative electrode unit was crimped to the positive electrode unit so that the separator 30 was in contact with the positive electrode 10. Then, the opening of the positive electrode can 12 was fitted to seal the positive electrode can 12 and the negative electrode can 22, and the resultant was allowed to stand at 25°C for 7 days to obtain nonaqueous electrolyte secondary batteries of Experimental Examples 1 to 7, each having a different concentration of supporting salt (LiFSI) contained in the electrolyte. As described above, the nonaqueous electrolyte secondary batteries of the respective experimental examples had different amounts of supporting electrolyte contained in the electrolyte, and the number of samples (number of samples produced) n was set to 3 for each example.
[0133] (Evaluation method) The discharge capacity of each of the nonaqueous electrolyte secondary batteries of Experimental Examples 1 to 7 having each supporting salt concentration was measured at discharge currents of 1.0 mA and 7.0 mA. The discharge cut-off voltage was 1.0 V, and the results are shown in the graphs of FIG. 3A (discharge current: 1.0 mA) and FIG. 3B (discharge current: 7.0 mA), respectively.
[0134] Furthermore, the discharge capacity of each of the nonaqueous electrolyte secondary batteries of Experimental Examples 1 to 7 was measured when the discharge current was changed in 1 mA increments within the range of 1 mA to 8 mA. The discharge cut-off voltage was set to 1.0 V, and the results are shown in the graph of Fig. 4. Note that the graph of Fig. 4 shows the average value of n=3 for each Experimental Example as the discharge capacity.
[0135] In addition, for the nonaqueous electrolyte secondary batteries of Experimental Examples 1 to 7, the capacity-increasing effect when the concentration of the supporting salt contained in the electrolyte was changed was expressed as a relative value (%) when the discharge capacity when the supporting salt concentration was 1 M (1 mol / L) was taken as "1", and the results when the discharge cut-off voltage was 2.0 V and 1.0 V are shown in the graphs of Fig. 5A (discharge cut-off voltage: 2.0 V) and Fig. 5B (discharge cut-off voltage: 1.0 V), respectively. Note that the graphs of Fig. 5A and Fig. 5B also show the capacity-increasing effect as an average value of n=3 in each experimental example.
[0136] [Experimental Examples 11-17] 2, a coin-type nonaqueous electrolyte secondary battery was fabricated having a structure in which a positive electrode 110 was disposed in a storage container 102 so as to cover the entire surface of an inner bottom 112b of a positive electrode can 112, and a gasket 140 was interposed between an inner part 112c of the positive electrode can 112 and the positive electrode 110 and a negative electrode can 122 to provide insulation and sealing. In addition, in Experimental Examples 11 to 17, an electrolyte solution was prepared with the composition shown below to fabricate a nonaqueous electrolyte secondary battery. In this experimental example, in the cross-sectional view shown in FIG. Outside diameter A coin-type (920 type) nonaqueous electrolyte secondary battery (lithium secondary battery) with a diameter of 9.5 mm and a thickness of 2.0 mm was fabricated.
[0137] In Experimental Examples 11 to 17, the electrolyte solutions prepared in Experimental Examples 1 to 7 and having the same compositions as those prepared in Experimental Examples 1 to 7 were used. The positive electrode 110 was also made of the same commercially available lithium manganese oxide (Li 1.14 Co 0.06 Mn 1.80 O4) was mixed with graphite as a conductive additive and polyacrylic acid as a binder in equal proportions to form a positive electrode mixture. Next, 115 mg of the obtained positive electrode mixture was applied to 2 The mixture was pressed at a pressure of 1000 MPa and molded into a disk-shaped pellet having a diameter (φ) of 8.9 mm and a thickness (t) of 0.67 mm.
[0138] Next, the obtained pellet (positive electrode 110) was adhered to the entire surface of the inner bottom 112b of a positive electrode can 112 made of stainless steel (SUS329J4L: t = 0.2 mm) using a carbon-containing conductive resin adhesive, and these were integrated to form a positive electrode unit, which was then dried by heating under reduced pressure in the atmosphere at 120°C for 11 hours. A sealant was then applied to the inner surface of opening 112a of positive electrode can 112 in the positive electrode unit.
[0139] Next, for the negative electrode 120, similar to the negative electrode active materials used in Experimental Examples 1 to 7, SiO powder whose entire surface was covered with carbon was prepared, and graphite as a conductive agent and polyacrylic acid as a binder were mixed with this negative electrode active material in the same ratio to prepare a negative electrode mixture. Next, 15.1 mg of the obtained negative electrode mixture was applied to 2 The mixture was pressed into a disk-shaped pellet having a diameter (φ) of 6.7 mm and a thickness (t) of 0.25 mm.
[0140] Next, similarly to Experimental Examples 1 to 7, the obtained pellet (negative electrode 120) was adhered to the inner top 122b of a negative electrode can 122 made of stainless steel (Cu-SUS304-Ni clad can: t = 0.2 mm) using a conductive resin adhesive containing carbon as a conductive filler, and these were integrated to form a negative electrode unit, which was then dried by heating under reduced pressure in a vacuum at 160°C for 11 hours. Then, a lithium foil 160 punched into a disk shape having a diameter (φ) of 6.1 mm and a thickness (t) of 0.38 mm was further pressure-bonded onto the pellet-shaped negative electrode 120 to form a lithium-negative electrode laminate.
[0141] Next, similarly to Experimental Examples 1 to 7, a nonwoven fabric made of glass fibers was dried and then punched into a disk shape with a diameter (φ) of 7.4 mm to form separator 130. This separator 130 was placed on lithium foil 160 that had been pressure-bonded onto negative electrode 120, and then a polypropylene gasket 140 was placed in the opening of negative electrode can 122.
[0142] Next, the positive electrode can 112 and the negative electrode can 122 are charged with the above-mentioned procedure. Manufacturing Each battery was filled with 30 μL of the electrolyte solution in total. For each of the seven types of electrolyte solutions (Experimental Examples 11 to 17: concentrations similar to those of Experimental Examples 1 to 7) prepared by changing the concentration of the supporting salt, the above-mentioned components constituting the nonaqueous electrolyte secondary battery were prepared, and the electrolyte solution was filled into the positive electrode can 112 and the negative electrode can 122, respectively.
[0143] Next, the negative electrode unit was crimped to the positive electrode unit so that the separator 130 was in contact with the positive electrode 110, and the opening of the positive electrode can 112 was fitted to seal the positive electrode can 112 and the negative electrode can 122.Then, the batteries were allowed to stand at 25°C for 7 days to obtain nonaqueous electrolyte secondary batteries of Experimental Examples 11 to 17, each having a different concentration of supporting salt (LiFSI) contained in the electrolyte. For each of the nonaqueous electrolyte secondary batteries of Experimental Examples 11 to 17, the number of samples (number of samples fabricated) was set to n=3.
[0144] Then, for the obtained nonaqueous electrolyte secondary batteries of Experimental Examples 11 to 17, the discharge capacity was measured at discharge currents of 1.0 mA and 7.0 mA and at a discharge cut-off voltage of 1.0 V, similarly to Experimental Examples 1 to 7, and the results are shown in the graphs of FIG. 6A (discharge current: 1.0 mA) and FIG. 6B (discharge current: 7.0 mA), respectively.
[0145] As in Experimental Examples 1 to 7, the capacity-increasing effect of the nonaqueous electrolyte secondary batteries of Experimental Examples 11 to 17 when the concentration of the supporting salt contained in the electrolyte was changed was shown in the graphs of Figures 7A and 7B, respectively. As in Experimental Examples 1 to 7, the capacity-increasing effect of Experimental Examples 11 to 17 was expressed as a relative value (%) when the discharge capacity when the supporting salt concentration was 1M (1 mol / L) was set to "1", and the results when the discharge cut-off voltage was 2.0V and 1.0V were shown in the graphs of Figures 7A (discharge cut-off voltage: 1.0V) and 7B (discharge cut-off voltage: 2.0V), respectively. Also in the graphs of Figures 7A and 7B, the capacity-increasing effect was shown as an average value of n=3 in each experimental example.
[0146] [Experimental Examples 21-27] 2, a coin-type nonaqueous electrolyte secondary battery was fabricated having a structure in which a positive electrode 110 was disposed in a storage container 102 so as to cover the entire surface of an inner bottom portion 112b of a positive electrode can 112, and a gasket 140 was interposed between an inner portion 112c of the positive electrode can 112 and the positive electrode 110 and the negative electrode can 122 to provide insulation and sealing. In addition, in Experimental Examples 21 to 27, an electrolyte solution was prepared with the composition shown below to fabricate a nonaqueous electrolyte secondary battery. In this experimental example, in the cross-sectional view shown in FIG. Outside diameter A coin-type (920 type) nonaqueous electrolyte secondary battery (lithium secondary battery) with a diameter of 9.5 mm and a thickness of 2.0 mm was fabricated.
[0147] In Experimental Examples 21 to 27, the electrolyte solutions used had the same compositions as those prepared in Experimental Examples 1 to 7 and Experimental Examples 11 to 17. The positive electrode 110 was made of commercially available lithium manganese oxide (Li4Mn5O 12 The positive electrode active material was mixed with graphite as a conductive additive and polyacrylic acid as a binder in a ratio of lithium manganese oxide:graphite:polyacrylic acid = 90:8:2 (mass ratio) to prepare a positive electrode mixture. Next, 98.6 mg of the obtained positive electrode mixture was 2The mixture was pressed at a pressure of 1000 MPa and molded into a disk-shaped pellet having a diameter (φ) of 8.9 mm and a thickness (t) of 0.67 mm.
[0148] Next, similarly to Experimental Examples 11 to 17, the obtained pellet (positive electrode 110) was adhered to the entire surface of the inner bottom 112b of a positive electrode can 112 made of stainless steel (SUS329J4L: t = 0.2 mm) using a carbon-containing conductive resin adhesive, and these were integrated to form a positive electrode unit, which was then dried by heating under reduced pressure in the atmosphere at 120°C for 11 hours. A sealant was then applied to the inner surface of opening 112a of positive electrode can 112 in the positive electrode unit.
[0149] Next, a negative electrode active material made of SiO powder not coated with carbon was prepared as the negative electrode 120, and graphite as a conductive agent and polyacrylic acid as a binder were mixed with this negative electrode active material in a ratio of 54:44:2 (mass ratio) to prepare a negative electrode mixture. Next, 15.1 mg of the obtained negative electrode mixture was applied to 2 The mixture was pressed into a disk-shaped pellet having a diameter (φ) of 6.7 mm and a thickness (t) of 0.25 mm.
[0150] Next, similarly to Experimental Examples 11 to 17, the obtained pellet (negative electrode 120) was adhered to the inner top 122b of a negative electrode can 122 made of stainless steel (Cu-SUS304-Ni clad can: t = 0.2 mm) using a conductive resin adhesive containing carbon as a conductive filler, and these were integrated to form a negative electrode unit, which was then dried by heating under reduced pressure in a vacuum at 160°C for 11 hours. Then, a lithium foil 160 punched into a disk shape having a diameter (φ) of 6.1 mm and a thickness (t) of 0.38 mm was further pressure-bonded onto the pellet-shaped negative electrode 120 to form a lithium-negative electrode laminate.
[0151] Next, similarly to Experimental Examples 11 to 17, a nonwoven fabric made of glass fiber was dried and then punched into a disk shape with a diameter (φ) of 7.4 mm to form separator 130. This separator 130 was placed on lithium foil 160 that had been pressure-bonded onto negative electrode 120, and then a polypropylene gasket 140 was placed in the opening of negative electrode can 122.
[0152] Next, the positive electrode can 112 and the negative electrode can 122 are charged with the above-mentioned procedure. Manufacturing Each battery was filled with 30 μL of the electrolyte solution prepared in total. For each of the seven types of electrolyte solutions (Experimental Examples 21 to 27: concentrations similar to those of Experimental Examples 1 to 7 and Experimental Examples 11 to 17) prepared by changing the concentration of the supporting salt, the above-mentioned components constituting the nonaqueous electrolyte secondary battery were prepared, and the electrolyte solution was filled into the positive electrode can 112 and the negative electrode can 122, respectively.
[0153] Next, similarly to Experimental Examples 11 to 17, the negative electrode unit was crimped to the positive electrode unit so that the separator 130 was in contact with the positive electrode 110, and the opening of the positive electrode can 112 was fitted to seal the positive electrode can 112 and the negative electrode can 122. The batteries were then left to stand at 25°C for 7 days to obtain nonaqueous electrolyte secondary batteries of Experimental Examples 21 to 27, each having a different concentration of supporting salt (LiFSI) contained in the electrolyte. The number of samples (number of samples fabricated) n of the nonaqueous electrolyte secondary batteries of Experimental Examples 21 to 27 was also set to 3.
[0154] Then, for the obtained nonaqueous electrolyte secondary batteries of Examples 21 to 27, similarly to Examples 1 to 7 and Examples 11 to 17, the discharge capacity was measured at discharge currents of 1.0 mA and 7.0 mA and at a discharge cut-off voltage of 1.0 V, and the results are shown in the graphs of FIG. 8A (discharge current: 1.0 mA) and FIG. 8B (discharge current: 7.0 mA), respectively.
[0155] In addition, for the nonaqueous electrolyte secondary batteries of Experimental Examples 21 to 27, the capacity-increasing effect when the concentration of the supporting salt contained in the electrolyte was changed was shown in the graphs of Figures 9A and 9B, respectively, in the same manner as in Experimental Examples 1 to 7 and Experimental Examples 11 to 17. In Experimental Examples 21 to 27, the capacity-increasing effect was expressed as a relative value (%) when the discharge capacity when the supporting salt concentration was 1M (1 mol / L) was set to "1", and the results when the discharge cut-off voltage was 1.0V and 2.0V were shown in the graphs of Figures 9A (discharge cut-off voltage: 1.0V) and 9B (discharge cut-off voltage: 2.0V), respectively, in the same manner as in Experimental Examples 1 to 7 and Experimental Examples 11 to 17. In addition, the capacity-increasing effect was shown in the graphs of Figures 9A and 9B, respectively, when n=3 in each experimental example was used.
[0156] [Experimental Examples 31-37] In Experimental Examples 31 to 37, coin-type nonaqueous electrolyte secondary batteries were fabricated with the same specifications as those in Experimental Examples 1 to 7, in which the storage container 2 had a structure in which a gasket 40 was interposed between the inner bottom 12b and the inner part 12c of the positive electrode can 12 and the negative electrode can 22 to insulate and seal the storage container 2 as shown in Fig. 1. That is, in Experimental Examples 31 to 37, experiment An electrolyte solution was prepared with the same composition corresponding to Examples 1 to 7, and in the cross-sectional view shown in FIG. Outside diameter A coin-type (920 type) nonaqueous electrolyte secondary battery (lithium secondary battery) with a diameter of 9.5 mm and a thickness of 2.0 mm was fabricated.
[0157] In Experimental Examples 31 to 37, a high temperature and humidity storage test (HHTS) was performed using a commercially available high temperature and humidity constant tester to confirm the change in internal resistance during the high temperature and humidity storage period, and the results are shown in the graph of Fig. 10 A. In Experimental Examples 31 to 37, the rate of increase in the internal resistance from the initial value for the same high temperature and humidity storage period was confirmed, and the results are shown in the graph of Fig. 10B.
[0158] The conditions for the high temperature and high humidity storage test were as follows: the nonaqueous electrolyte secondary batteries in Experimental Examples 31 to 37 were short-circuited via a resistor of 18 kΩ to put them into an overdischarged state; under this state, the temperature was 60°C, the humidity was 90% RH, and the tests were performed for periods of 7 days, 14 days, 21 days, 28 days, and 40 days. The internal resistance was measured by an AC method at a frequency of 1 kHz.
[0159] In addition, in Experimental Examples 31 to 37, a high temperature and humidity storage test (HHTS) was performed using a commercially available high humidity constant temperature tester under the following conditions, and the changes in discharge capacity and capacity retention rate with respect to the initial values during the high temperature and humidity storage period were confirmed, and the results are shown in the graphs of Figures 11A and 11B. The high temperature and humidity storage conditions were the same as those described above, except that the period was 28 days and 40 days.
[0160] In measuring the discharge capacity, the battery was first charged at room temperature (25°C) under the conditions of a voltage of 3.1 V, a current of 0.3 mA, and a charging time of 120 hours, and then discharged at a temperature of 25°C, a current of 50 μA, and a final voltage of 2 V, and the value was taken as the initial capacity. The nonaqueous electrolyte secondary battery after the high temperature and high humidity storage test was charged and discharged under the same conditions as the initial capacity, and the discharge capacity after the test was determined as the capacity retention rate relative to the initial capacity.
[0161] <Evaluation Results> As shown in the graphs of Figures 3A and 3B, in Experimental Examples 1 to 7 in which a nonaqueous electrolyte secondary battery (see Figure 1) having a structure in which a gasket 40 is interposed between the inner bottom 12b and inner part 12c of the positive electrode can 12 and the negative electrode can 22 to provide an insulating and sealed structure was used, and experiments were performed by changing the content of LiFSI contained in the electrolyte. It was confirmed that a large discharge capacity was obtained when the LiFSI content was in the range of 2 to 5 mol / L (Experimental Examples 2 to 5). In particular, it was confirmed that a very large discharge capacity was obtained when the LiFSI content in the electrolyte was 3 to 4 mol / L (Experimental Examples 3 and 4). This is also clear from the graph showing the relationship between discharge current and capacity shown in Figure 4. Furthermore, as shown in the graphs of Figures 5A and 5B, in Experimental Examples 1 to 7, when the LiFSI content was in the range of 2 to 5 mol / L (Experimental Examples 2 to 5), a large capacity-increasing effect was observed. In particular, when the discharge end voltage was 1.0 V, it was confirmed that when the LiFSI content in the electrolyte was 3 to 4 mol / L (Experimental Examples 3 and 4), a larger capacity-increasing effect was obtained.
[0162] The positive electrode 110 is disposed so as to cover the entire inner bottom portion 112b of the positive electrode can 112, and the inner portion 112c of the positive electrode can 112 and the positive electrode 110 In Experimental Examples 11 to 17, in which experiments were performed using a nonaqueous electrolyte secondary battery (see FIG. 2) having a structure insulated and sealed by interposing a gasket 140 between the negative electrode can 122 and the negative electrode can 123, and the content of LiFSI in the electrolyte was varied, it was confirmed that a large discharge capacity was obtained when the LiFSI content was in the range of 2 to 5 mol / L (Experimental Examples 12 to 15), as shown in the graphs of FIG. 6A and FIG. 6B. Furthermore, in Experimental Examples 11 to 17, it was confirmed that a very large discharge capacity was obtained, particularly when the LiFSI content in the electrolyte was 2 to 3 mol / L (Experimental Examples 12 and 13). Furthermore, as shown in the graphs of Figures 7A and 7B, in Experimental Examples 11 to 17, when the LiFSI content was in the range of 2 to 5 mol / L (Experimental Examples 12 to 15), a large capacity-increasing effect was observed, and it was confirmed that, in particular, when the LiFSI content in the electrolyte was 2 to 3 mol / L (Experimental Examples 12 and 13), a larger capacity-increasing effect was stably obtained.
[0163] 2, in Experimental Examples 21 to 27 in which the composition of the positive electrode active material used in the positive electrode 110 and the particle structure of the negative electrode active material and the composition of the negative electrode mixture used in the negative electrode 120 were changed, it was confirmed that a large discharge capacity was obtained when the LiFSI content was in the range of 2 to 5 mol / L (Experimental Examples 22 to 25), as shown in the graphs of Figures 7A and 7B. It was also confirmed that in Experimental Examples 21 to 27, particularly when the LiFSI content in the electrolyte was 2 to 3 mol / L (Experimental Examples 22 and 23), a very large discharge capacity was obtained. Furthermore, as shown in the graphs of Figures 9A and 9B, in Experimental Examples 21 to 27, when the LiFSI content was in the range of 2 to 5 mol / L (Experimental Examples 22 to 25), a significant capacity-increasing effect was observed, and it was confirmed that, in particular, when the LiFSI content in the electrolyte was 2 to 3 mol / L (Experimental Examples 22 and 23), a significant capacity-increasing effect was obtained.
[0164] 10A, in Experimental Examples 31 to 37, in which experiments were conducted using a nonaqueous electrolyte secondary battery (see FIG. 1) having a structure in which a gasket 40 was interposed between the inner bottom 12b and the inner part 12c of the positive electrode can 12 and the negative electrode can 22 to provide an insulating and sealed structure, and the content of LiFSI in the electrolyte was varied, it was confirmed that the internal resistance was significantly reduced to about 180Ω to 315Ω, particularly when the LiFSI content was in the range of 4 to 7 mol / L (Experimental Examples 34 to 37). It is clear from the curves shown in the graph of FIG. 10A that in Experimental Examples 34 to 37, an increase in internal resistance was suppressed regardless of whether the storage period was 7 days, 14 days, 21 days, 28 days, or 40 days.
[0165] 10B, it was confirmed that the rate of increase in internal resistance was significantly suppressed in Experimental Examples 31 to 37, as described above, particularly in Experimental Examples 34 to 37, in which the LiFSI content was in the range of 4 to 7 mol / L. It is clear that the rate of increase in internal resistance was significantly suppressed in these Experimental Examples 34 to 37, regardless of whether the storage period was 7 days, 14 days, 21 days, 28 days, or 40 days.
[0166] Furthermore, in Experimental Examples 31 to 37, as described above, it was confirmed that, particularly in Experimental Examples 34 to 37 in which the LiFSI content was in the range of 4 to 7 mol / L, the decrease in discharge capacity after storage in a high-temperature, high-humidity environment and in an overdischarged state was suppressed. 11A and 11B, it can be seen that the battery had a sufficient discharge capacity (capacity after storage) compared to the initial capacity whether the storage period was 28 days or 40 days. Also, in Experimental Examples 34 to 37, the capacity retention rate after storage in a high-temperature, high-humidity environment and in an overdischarged state was 68% to 93% when the storage period was 28 days, and 45% to 85% when the storage period was 40 days, which shows a higher capacity retention rate than that of a conventional nonaqueous electrolyte secondary battery.
[0167] As described above, the detailed mechanism by which the electrical characteristics (overdischarge characteristics) of a nonaqueous electrolyte secondary battery after storage under high temperature, high humidity and overdischarge conditions are improved by the concentration of LiFSI having excellent electrical conductivity within the above range is not clear. On the other hand, the results of each of the above experimental examples confirmed that, if the concentration of LiFSI is within the above range, deterioration of the nonaqueous electrolyte secondary battery can be prevented even when overdischarge occurs.
[0168] From the results of the above-described examples (Experimental Examples 1 to 7, 11 to 17, and 21 to 27), it is clear that by using an electrolyte solution having a composition defined in the present invention and combining it with a configuration in which the internal arrangement of each battery element is optimized, a nonaqueous electrolyte secondary battery can be obtained that maintains sufficient discharge capacity even when discharging at the mA level and has excellent high output characteristics and high capacity characteristics despite its small size. Furthermore, from the results of the above examples (Experimental Examples 31 to 37), it is clear that by using a supporting salt for the electrolyte containing LiFSI, which has excellent electrical conductivity, in the above-mentioned molar ratio range, and further combining this with a configuration in which the internal arrangement structure of each battery element is optimized, the electrical characteristics (overdischarge characteristics) after storage of the nonaqueous electrolyte secondary battery under high temperature, high humidity and overdischarge conditions are further improved, making it possible to more effectively prevent deterioration of the nonaqueous electrolyte secondary battery even if overdischarge occurs. [Industrial Applicability]
[0169] The nonaqueous electrolyte secondary battery of the present invention can supply a large current over a wide temperature range, can maintain a sufficient discharge capacity even when discharging at the mA level, and can obtain high output characteristics and high capacity characteristics despite its small size. Therefore, by applying the present invention to nonaqueous electrolyte secondary batteries used in the fields of various electronic devices, for example, and providing them for use as main power sources in addition to backup power sources, it can contribute to the miniaturization and performance improvement of various electronic devices, etc. [Explanation of symbols]
[0170] 1,100…Nonaqueous electrolyte secondary battery 2,102…Storage containers 10,110...Positive electrode 12,112…Positive electrode can 12a, 112a...opening 12b,112b…Inner bottom 12c, 112c…inner part 14,114...Positive electrode current collector 20,120…Negative electrode 22,122…Anode can 22a...Tip 22b,122b…Inner top 24...Negative electrode current collector 30…Separator 40…Gasket 41...Annular groove 50...Electrolyte 60…Lithium foil
Claims
1. a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator disposed between the positive electrode and the negative electrode; an electrolyte solution including an organic solvent and a supporting salt; a storage container having an internal storage space in which the positive electrode, the negative electrode, the separator, and the electrolyte are disposed; At least one of the positive electrode and the negative electrode is in the form of a pellet containing an active material, a conductive additive, and a binder, The separator is made of a nonwoven glass fiber fabric, The electrolytic solution contains, as the organic solvent, a mixed solution of propylene carbonate (PC), ethylene carbonate (EC), and dimethoxyethane (DME) in a volume ratio range of {PC:EC:DME}={0.5-1.5:0.5-1.5:1-3}, and contains, as the supporting salt, lithium bis(fluorosulfonyl)imide (LiFSI) in an amount of more than 2 (mol / L) and not more than 7 (mol / L).
2. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the electrolyte contains the supporting salt lithium bis(fluorosulfonyl)imide (LiFSI) at 4 to 7 (mol / L).
3. The storage container includes: A cylindrical positive electrode can with a bottom; a negative electrode can that is fixed to the opening of the positive electrode can with a gasket interposed therebetween and that forms an accommodation space between the negative electrode can and the positive electrode can, 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the battery is a coin-shaped container in which the storage space is sealed by crimping an opening of the positive electrode can to the negative electrode can.
4. 4. The nonaqueous electrolyte secondary battery according to claim 3, wherein the container is structured so as to be insulated and sealed by interposing the gasket between the inner bottom and inner side of the positive electrode can and the negative electrode can.
5. 5. The nonaqueous electrolyte secondary battery according to claim 4, wherein the electrolyte contains the supporting salt lithium bis(fluorosulfonyl)imide (LiFSI) at 3 to 4 (mol / L).
6. A positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator disposed between the positive electrode and the negative electrode; an electrolyte solution including an organic solvent and a supporting salt; a storage container having an internal storage space in which the positive electrode, the negative electrode, the separator, and the electrolyte are disposed; At least one of the positive electrode and the negative electrode is in the form of a pellet containing an active material, a conductive additive, and a binder, The separator is made of a nonwoven glass fiber fabric, The electrolytic solution contains, as the organic solvent, a mixed solution of propylene carbonate (PC), ethylene carbonate (EC), and dimethoxyethane (DME) in a volume ratio range of {PC:EC:DME}={0.5 to 1.5:0.5 to 1.5:1 to 3}, and contains, as the supporting salt, lithium bis(fluorosulfonyl)imide (LiFSI) at 2 to 7 (mol / L); The storage container includes: A cylindrical positive electrode can with a bottom; a negative electrode can that is fixed to the opening of the positive electrode can with a gasket interposed therebetween and that forms an accommodation space between the negative electrode can and the positive electrode can, the storage container is a coin-shaped container in which the storage space is sealed by crimping an opening of the positive electrode can to the negative electrode can, The nonaqueous electrolyte secondary battery is further characterized in that the storage container has a structure in which the positive electrode is disposed so as to cover the entire surface of an inner bottom portion of the positive electrode can, and the gasket is interposed between the inner side of the positive electrode can and between the positive electrode and the negative electrode can, thereby providing an insulating and sealed structure.
7. 7. The nonaqueous electrolyte secondary battery according to claim 6, wherein the electrolyte contains the supporting salt lithium bis(fluorosulfonyl)imide (LiFSI) at 2 to 3 (mol / L).
8. The positive electrode contains at least Li as the positive electrode active material. 1+x Co y Mn 2-x-y O 4 8. The nonaqueous electrolyte secondary battery according to claim 1, further comprising a lithium manganese oxide having the formula (0≦x≦0.33, 0<y≦0.2).
9. The negative electrode contains, as the negative electrode active material, SiO X 9. The nonaqueous electrolyte secondary battery according to claim 1, further comprising: (0<X<2).
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2017224430A
Power storage device and electrode
JP2021028957A
Nonaqueous electrolyte secondary battery
WO2016143543A1
Non-aqueous electrolyte solution for lithium secondary battery and lithium secondary battery comprising same
WO2021033987A1